Transcranial direct current electrical stimulation for the treatment of interstitial cystitis: A study protocol. (July 2021) - Dutra, Larissa Ramalho Dantas Varella; Silva-Filho, Edson; Oliveira, Maiara Costa; Paiva Tavares, Brenda Nayara; Pegado, Rodrigo; Micussi, Maria Thereza Babosa Albuquerque Cabral
Abstract: Background: Interstitial cystitis or painful bladder syndrome is a chronic disorder that presents an unknown etiology, with no generally accepted treatment. Although there is no gold standard treatment, transcranial direct current stimulation (tDCS) has shown efficacy in several chronic pain syndromes with decrease in pain, and improved functionality and mood. tDCS could be a safe, ease to use, and low-cost complementary intervention for patients with interstitial cystitis. Aim: This study will investigate the effects of a tDCS protocol on pain, functionality, and mood in patients with interstitial cystitis. Methods: A randomized controlled clinical trial with two arms. Women will be randomized into two groups: active or sham. Anodal tDCS over the primary motor cortex will be performed for 5 consecutive days with an intensity of 2 mA for 20 min. Participants will be evaluated five times: 1 week before intervention; on the 5 th day of tDCS; and 1, 6, and 12 months after the last day of tDCS. The outcomes will be assessed using the numeric rating scale, McGill pain questionnaire, positive and negative affect scale, international consultation on incontinence questionnaire for female lower urinary tract symptoms, Hamilton anxiety scale, six-minute walk test, patient global impression of change, and voiding diary. Discussion: Only the active group will be expected to show decreased pain. The results of this trial will be the first step in the use of neuromodulation in interstitial cystitis and will provide additional data to support new studies with tDCS.